Sufism and Kenosis: The Basis of One’s Resilience as a Zoom Politicon - Martina Novalina; Erastus Sabdono; Indria Samego (Teosofia: Indonesian Journal of Islamic Mysticism, 2021)
The COVID-19 pandemic has brought humans into a new civilization, where Zoom meeting is no longer just an application but a changing pattern of human interaction with each other. This change, of course, requires adaptation, and not a few end up having problems due to Work From Home. Zoom applications risked two times of experiencing fatigue in students and four times of experiencing stress and also having issues in disruption of social functioning. This article aims to provide a solution to a person's resilience as a social being in the zoom era (zoom politicon) by applying Sufism and kenosis values. The approach used is library research. Through this study, we can see that some of the values in Sufism and kenosis have become the basis for a person to survive all challenges in life, especially amid fatigue doing activity online. These current values also protect a person from being caught up in a sin that eventually perishes. Human values as a part of zoom politicon must still be put forward to reflect one's spiritual journey to God.